European Monetary Union and International Capital Markets : Structural Implications and Risks - Schinasi, Garry (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the structural implications of EMU for international capital markets. It discusses the potential size of euro capital markets and the existing roles of European currencies in international capital markets. The paper also examines the euro's impact on international securities markets, including the role of the ECB, the evolution of EMU securities markets, and aspects of systemic risk management. The implications for wholesale and retail banking markets are also discussed, as are the broader implications of the introduction of the euro for changes in international capital flows, international portfolios, and by implication exchange rates.